(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article presents an opinion on the integrative principles of teaching pedagogical sciences in the context of glocalization. According to the principle of information asymmetry in science, it can be concluded that in political, social and economic spheres, decision-making, just like in the field of environmental protection, often (perhaps always) takes place in conditions of uncertainty.